Hybridizing Heritage: Integrating Balinese Cultural Logic into Resilient Urban Identity in Semarapura, Bali - Ngakan Ketut Acwin Dwijendra (DIMENSI (Journal of Architecture and Built Environment), 2025)
This research examines urban spatial and cultural identity in Semarapura, the former capital of Klungkung Regency, Bali, through the lens of resilient urbanism. It has three objectives of research to reach: (1) identifying some cultural and design key-elements referring to Balinese spatial philosophy; (2) investigating the breaking points in spaces and tensions due to the pressures of modernization; (3) suggesting a hybrid framework for identities that maintain continuity but also flexibility in spaces. A qualitative approach was used, based on fieldwork observations, semi-structured interviews with local actors (n = 30), and document analysis of planning tools and historical maps. The analytic tools were urban morphological mapping, thematic content analysis, and a comparative matrix of traditional and modern spatial intersections. It shows the persistence of symbolic structures (Catuspatha, Tri Mandala zoning, and Bale Banjar), residing in spatial memory and urban form. But a myriad of challenges, such as commercial overreach, scattered signage, and lax regulation, have disrupted ceremonial routes and architectural harmony. Yet, community-generated innovations and adaptive design practices signal cultural resilience through the adoption of Asta Kosala Kosali in the home, green infrastructure harkening back to Tri Hita Karana, and mural revitalizations that act as performative identity tools. The research introduces a hybrid identity model guided by cultural logic and calls for policy change to ensure that both spatial-cultural indicators are considered in urban policies. The Semarapura case demonstrates that situational design and local action can work together to create liveable and sustainable cities in heritage cities of the Global South.